Maximum extent and readvance dynamics of the Irish Sea Ice Stream and Irish Sea Glacier since the Last Glacial Maximum. (7th May 2021) - Scourse, J. D.; Chiverrell, R. C.; Smedley, R. K.; Small, D.; Burke, M. J.; Saher, M.; Van Landeghem, K. J. J.; Duller, G. A. T.; Cofaigh, C. Ó; Bateman, M. D.; Benetti, S.; Bradley, S.; et al.
ABSTRACT: The BRITICE‐CHRONO Project has generated a suite of recently published radiocarbon ages from deglacial sequences offshore in the Celtic and Irish seas and terrestrial cosmogenic nuclide and optically stimulated luminescence ages from adjacent onshore sites. All published data are integrated here with new geochronological data from Wales in a revised Bayesian analysis that enables reconstruction of ice retreat dynamics across the basin. Patterns and changes in the pace of deglaciation are conditioned more by topographic constraints and internal ice dynamics than by external controls. The data indicate a major but rapid and very short‐lived extensive thin ice advance of the Irish Sea Ice Stream (ISIS) more than 300 km south of St George's Channel to a marine calving margin at the shelf break at 25.5 ka; this may have been preceded by extensive ice accumulation plugging the constriction of St George's Channel. The release event between 25 and 26 ka is interpreted to have stimulated fast ice streaming and diverted ice to the west in the northern Irish Sea into the main axis of the marine ISIS away from terrestrial ice terminating in the English Midlands, a process initiating ice stagnation and the formation of an extensive dead ice landscape in the Midlands.